2021
DOI: 10.1101/2021.03.22.436378
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental evolution reveals post-transcriptional regulation as a novel driver ofLeishmaniafitness gain

Abstract: The protozoan parasite Leishmania donovani causes fatal human visceral leishmaniasis in absence of treatment. Genome instability has been recognized as a driver in Leishmania fitness gain in response to environmental change or chemotherapy. How genome instability generates beneficial phenotypes despite potential deleterious gene dosage effects is unknown. Here we address this important open question applying experimental evolution and integrative systems approaches on parasites adapting to in vitro culture. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
(165 reference statements)
0
3
0
Order By: Relevance
“…In the process of catabolism of amino acids via the Ehrlich pathway, the gene encoding a putative alpha keto acid decarboxylase was upregulated. This pathway is a source of alpha keto acids such as pyruvate during conditions of nutritional starvation [44]. The biological process, "modulation of process of other organism", represented by genes encoding a major metalloendopeptidase called Leishmanolysin/GP63, was also upregulated.…”
Section: Go and Gsea Analysismentioning
confidence: 99%
“…In the process of catabolism of amino acids via the Ehrlich pathway, the gene encoding a putative alpha keto acid decarboxylase was upregulated. This pathway is a source of alpha keto acids such as pyruvate during conditions of nutritional starvation [44]. The biological process, "modulation of process of other organism", represented by genes encoding a major metalloendopeptidase called Leishmanolysin/GP63, was also upregulated.…”
Section: Go and Gsea Analysismentioning
confidence: 99%
“…It would be interesting to analyse quantitative proteomic data in the aneuploid clones to see if there is a compensatory mechanism at this stage or if the parasite can deal with chromosome-wide 50% increase in protein level. In Leishmania parasites, several studies have also shown an overall correlation of ploidy and transcription [53,54,55], albeit with gene dosage-independent fluctuations for some chromosomes and indications of regulatory mechanisms compensating at the protein expression level [55]. On a practical matter, the observation that there is a direct correlation of mRNA transcript level and ploidy, indicates that comparative RNA-seq data could be used to directly determine deviations from euploidy in T. brucei field isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Although the transcriptome size was diminished in all quiescent states measured compared to proliferative cells, the transcriptome composition revealed particular mRNAs whose proportion increased or decreased relative to others during quiescence. Since the transcriptome has a moderate correlation with levels of protein expression [40,41], comparative transcriptome composition can provide insights into the biological processes associated with quiescence. We specifically sought changes found in quiescent cells irrespective of the life cycle stage or stimulus, and using GO/GSEA analysis identified three main functional categories as being upregulated: autophagy, proteolysis associated with leishmanolysin (GP63), and amastin/amastin-like proteins.…”
Section: Discussionmentioning
confidence: 99%